Prevalence of Enteropathogens and Virulence Traits in Brazilian Children With and Without Diarrhea - Merino, Victor R.; Nakano, Viviane; Delannoy, Sabine; Fach, Patrick; Alberca, Gabriela G. F.; Farfan, Mauricio J.; Piazza, Roxane M. F.; Avila-Campos, Mario J. (Frontiers in Cellular and Infection Microbiology, 2020)
The use of molecular diagnostics for pathogen detection in epidemiological studies have allowed us to get a wider view of the pathogens associated with diarrhea, but the presence of enteropathogens in asymptomatic individuals has raised several challenges in understanding the etiology of diarrhea, and the use of these platforms in clinical diagnosis as well. To characterize the presence of the most relevant bacterial enteropathogens in diarrheal episodes, we evaluated here the prevalence of diarrheagenic E. coli pathotypes, Salmonella spp., and Yersinia enterocolitica in stool samples of children with and without diarrhea using real-time quantitative PCR (qPCR). We found that the presence of genetic markers associated with bacterial pathogens was significantly higher in stool samples from the diarrhea group compared to the control (P < 0.001). Bacterial loads in samples positive for eae and aggR markers were also determined. Compared to samples from asymptomatic children, a significantly higher number of copies of the eae gene were found in diarrhea samples. Also, the presence of genetic markers associated with STEC strains with clinical significance was evaluated in eae-positive samples by high-throughput real-time PCR. The data presented herein demonstrated that asymptomatic children of an urban area in Brazil might be enteropathogen reservoirs, especially for STEC.